Achieving long cycle sodium-ion storage by an "top-down" size control strategy on Sn-based anode. (1st July 2022) - Wang, Fangmin; Cao, Liyun; Su, Jiangming; Liu, Mengyu; Huang, Jianfeng; Li, Jiayin; He, Danyang; Wang, Yong; Xu, Zhanwei; Kajiyoshi, Koji; Liu, Yijun; Pan, Limin
Highlights: Ultra-small Sn nanoparticles (25 nm) were grown on the surface of carbon cloth by an "top-down" in-situ strategy. The "top-down" strategy employs in-situ phase transformation technology of Sn nanoparticles, decreasing the size of Sn nanoparticles from 125 to 25 nm successfully. The faster reaction kinetics and good structural stability promote the long cycle sodium-ion storage performance. Abstract: Size control is one of the important strategies to improve the sodium-ion storage performance of Sn-based anode materials. However, the traditional control strategy of "bottom-up" methods still needs to be improved because of their complex processes to obtain nanostructures in Sn anodes. Herein, a simple "top-down" strategy is adopted to realize ultra-small Sn nanoparticles (∼25 nm). This strategy employs in-situ phase transformation technology of Sn nanoparticles, decreasing the size of Sn nanoparticles from 125 to 25 nm successfully. Benefiting from this nanostructure, these ultra-small Sn nanoparticles achieve long cycle sodium-ion storage performance during cycling. As an anode material for sodium-ion batteries, the electrode exhibits a reversible capacity of 387.2 mAh g −1 after 500 cycles at a current density of 1 A g −1 . Further characterization shows that it has good kinetics performance and structural stability. This work can provide ideas toward the structural design of Sn-based anode to obtain high electrochemical performance in future.